The Influence of Pre-Existing Tension Cracks on the Stability of Unsupported Temporary Excavations in Stratified Hard Clays: Case Study of Corfu Island, Northwestern Greece - Panagiotis Pelekis; Anastasios Batilas; Spyridon Lainas; Nikolaos Depountis (Geosciences)
Slope failures in overconsolidated hard clays present significant geotechnical challenges, particularly in stratified formations prone to pre-existing discontinuities. Despite extensive research on residual shear strength and fissuring in stiff clays, the role of undetected tension cracks and their interaction with hydrogeological conditions in temporary excavations remains underexplored. This study addresses this research gap through a detailed case study of a slope failure during an unsupported residential excavation on Corfu Island, Greece. The investigation aimed to identify the failure mechanism, assess the influence of geological discontinuities and groundwater conditions, and evaluate the contribution of residual shear strength to slope stability. The methodology combined field observations, laboratory testing (including unconfined compression and ring shear tests), and numerical modelling using both finite element (FEM) and limit equilibrium (LEM) approaches. The results revealed that a nearly vertical, pre-existing fissure—acting as a tension crack—and water infiltration along the clay–sandstone interface significantly reduced the factor of safety, triggering a planar slide. Both FEM and LEM analyses indicated that critical conditions for failure were reached with a residual friction angle of 19°, inclined sandstone layers at 15–17°, and hydrostatic pressure from groundwater accumulation. This study demonstrates the compounded destabilizing effects of undetected discontinuities and water pressures in stratified hard clays and underscores the necessity of comprehensive geotechnical assessments for temporary excavations, even in seemingly stable formations.